Blast Diffusion by Different Shapes of Domes - Sahu, Ram Ranjan; Gupta, Pramod Kumar (Defence Science Journal, 2015)
Domes have been used since ancient times in constructions. These are effective structures in supporting loads for large span. Dome has an added advantage of having good looking in structural applications. Many shapes of domes are being used nowadays for residential, commercial, and industrial purposes. Specific purpose domes are also used for nuclear containment. Main threats to structures are from the bomb blast. Hence, domes too are to be designed to withstand effectively the pressure energy generated by the blast. A comparative theoretical study is proposed on the different shapes of domes having same weight and thickness. Various responses are estimated through numerical method after simulating blast and comparing their intensities. Defence Science Journal, Vol. 65, No. 1, January 2015, pp.77-82, DOI:http://dx.doi.org/10.14429/dsj.65.6908